Effect of the glycaemic index of pre-exercise carbohydrate meals on running performance - Wong, S. H. S.; Siu, P. M.; Lok, A.; Chen, Y. J.; Morris, J.; Lam, C. W. (European Journal of Sport Science, 2008)
The aim of this study was to examine the effect of pre-exercise low and high glycaemic index (GI) carbohydrate meals on running performance. Eight endurance-trained male runners (mean age 33 years, sx=1.7; VO2max 63 ml · kg-1 · min-1, sx=1.8) completed two trials separated by at least 7 days in a counterbalanced design. Two hours before they were to run and after an overnight fast, each participant consumed an isocaloric meal containing either low (gi=37) or high (gi=77) GI carbohydrate foods (2.4 MJ; 65% carbohydrate; 15% protein; 20% fat) that provided 1.5 g carbohydrate per kilogram of body mass in random order. Each trial consisted of a 21-km performance run on a level treadmill. The participants were required to run at 70% VO2max during the first 5 km of the run. They subsequently completed the remaining 16 km in as short a time as possible. All participants achieved a faster performance time after the consumption of the low GI meal (low vs. high GI: 98.7 min, sx=2 vs. 101.5 min, sx=2; P<0.01). Blood glucose and serum free fatty acids concentrations were higher throughout the performance run in the low GI trial. Serum insulin concentrations were higher in the high GI trial during the postpandial resting period. However, there were no differences between trials in serum insulin or blood lactate concentrations throughout exercise. Compared with the high GI trial, carbohydrate oxidation was 9.5% lower and fat oxidation was 17.9% higher during exercise in the low GI trial. In conclusion, our results indicate that compared with an isocaloric high GI meal, the consumption of a low GI meal 2 h before a 21-km performance run is a more effective means of improving performance time.